Simbolismo e trasformazione dello spazio domestico nel Modernismo inglese e in To the Lighthouse di Virginia Woolf - Pozzuoli, Cesare (Status Quaestionis, 2017)
This paper is aimed at observing the evolution in the representation of domestic spaces within the genre of the ‘family novel’ from the 19th century to Modernism. In the first part of this work, I approached the development of the ‘domestic novel’ from Victorian Realism to ‘High Modernism’ with particular reference to the idea of ‘familiar object’ from the 19th to the 20th century in English fiction. In particular I decided to analyze this subject with reference to Virginia Woolf’s To the Lighthouse (1927) comparing this novel with other works by the same author including Jacob’s Room and The Years published respectively in 1922 and 1937.